Analysis of the Reacquisition of Citizenship Loss Based on Indonesian Constitutional Law - Yuliya Safitri (Pelopor Publikasi Akademika, 2023)
In the democratic state and the rule of law, human rights protection is an essential principle. The fact that citizenship status is fundamental rights put consequences that the states and citizen has reciprocal relations which means states needs their citizens as well as citizens need states. States should ensure that no one in the states is left stateless. In order to avoid stateless, the State needs to be aware and anticipative which is reflected through legislation and administrative practices. In the Heidy Mariska case, the administrates neglected article 17c Law No. 62 Year 1958 on Citizenship which then results in diffusion of Heidy Mariska citizenship status so that she was stateless in the country she was born in. This paper analyse the implementation of the law on citizenship whether or not it reflects protection to citizenship status and anticipation of statelessness.